Tailoring mechanical properties of sol-gel hybrids for bone regeneration through polymer structure - Chung,J; Li,S; Stevens,MM; Georgiou,T; Jones,JR (Chemistry of Materials, 2016)
Bioglass was the first synthetic biomaterial that formed a chemical bond to bone. Although bioactive glass scaffolds can mimic bone’s porous structure, they are brittle. Sol–gel derived hybrids could overcome this problem because their nanoscale conetworks of silica and organic polymer have the potential to provide unique physical properties and controlled homogeneous biodegradation. Copolymers of methyl methacrylate (MMA) and 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) have been used as an organic source for hybrids to take advantage of their self-hardening property. However, the effect of well-defined poly(MMA-co-TMSPMA) architecture in the hybrid system has not been investigated. Here, linear, randomly branched, and star shaped methacrylate based copolymers were synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization method. These copolymers were then used to fabricate hybrids. The 3-D polymer structure had a significant effect on mechanical properties, providing higher strain to failure while maintaining a compressive strength similar to sol–gel glass. Star copolymer–SiO2 hybrids had a modulus of toughness 9.6-fold greater and Young’s modulus 4.5-fold lower than a sol–gel derived bioactive glass. During in vitro cell culture, MC3T3-E1 osteoblast precursor cells adhered on the surface regardless of the polymer structure. Introducing star polymers to inorganic–organic hybrids opens up possibilities for the fine-tuning physical properties of bone scaffold materials.